SUBJECTIVE REPORT OF DRIVING AND OBJECTIVE REAL-WORLD DRIVING HABITS IN OLDER ADULTS. (11th November 2018) - Phatak, V; Merickel, J; Frankel, E; Dawson, J; Rizzo, M
Abstract: Cognitive aging affects older driver performance, behavior, and awareness. Accurate self-monitoring is key to mitigation of driver risk though changes in driving habits and exposure. This study compared self- and partner-rating of driving habits to actual naturalistic driving data patterns in 79 legally-licensed, active older drivers (mean age 75.1; mean driving experience 58.2 years.) On induction, all drivers and their partners rated participant driving ability and changes in driving habits on scales of 1–7 on a Driving Habits Questionnaire. Participants underwent neuropsychological testing, generating a normalized neuropsychological composite index. Unobtrusive sensors and cameras ("Black Box" Systems) installed in participants' own vehicles captured continuous data, including metrics of vehicle acceleration, number of drives, and mean speed across drives for a three-month period. Vehicle acceleration exceedances (|a| >0.35g) flagged hard braking and poor vehicle control. Self-ratings (4–7 with a modal rating of 6) and partner ratings (3–7 with a modal rating of 7) of driving ability correlated with reported years of driving experience. Self-rating of driving restrictions such as in the rain, at night, etc. (rho=.244, p=.03) and partner rating (rho=.264, p=.02) correlated with the normalized neuropsychological composite index. There were no significant correlations between self-rating or partner rating of driving ability and age, performance on cognitive tests, or vehicle acceleration events. Results indicated older drivers with increased cognitive difficulties restricted their driving in at-risk situations (e.g., at night, ) even though these driving self-restrictions were notably not reflected in either patient or partner subjective report of driving ability.